Spectrophotometric determination of nitrite in cured meat products - Oliveira, Jessica Fernandes de [UNESP]; Silva, Uilian Ribeiro da; Abib Pastore, Victor Alessandro [UNESP]; Azevedo, Everton Cruz de [UNESP]; Campos, Glaucia Martins de [UNESP]; Goncalves da Silva, Felipe Chaimsohn [UNESP]; Raghiante, Fernanda [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2017)
The cured meat products have shown great expansion and high competitiveness in the last decade, since the consumption of meat products such as sausages, fresh sausages and mortadellas has become increasingly present in the food habits of the Brazilian population. Curing salts, such as sodium and potassium nitrate and nitrite, are widely used as food additives in the processing of meat products and have the purpose of preserving, enhancing or modifying the sensory properties of foods. The objective of this work was to determine the content of nitrite in cured meat products in the city of Avare - SP and region using the spectrophotometric method. The cured meat products used in the research were mortadellas, sausages and fresh sausages. We analyzed a total of 270 samples of sausages market from three different brands each. The determination of the nitrite ion was performed by the spectrophotometric method at 540 nm. The presence of nitrite was present in all samples of the meat products analyzed, whose average concentrations ranged from 29.25 ppm to 249.80 ppm. Among the cured meat products, the sausage brands A and C presented nitrite content higher than allowed in Brazilian legislation (maximum 150 ppm). It concludes that measures to control the production of fresh sausage and health education could be applied more rigorously in industries and commercial establishments in order to guarantee products of higher quality and safe as to the content of nitrite in its composition.
Keywords: Cured Meat Products; Fresh Sausage; Mortadellas; Nitrite; Sausage